2020
DOI: 10.1159/000506381
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glycemia on Choroidal Thickness in Different Stages of Diabetic Retinopathy

Abstract: Objective: The purpose of this study was to evaluate the influence of renal and glycemic parameters on choroidal thickness (CT) in patients with diabetes with and without diabetic retinopathy (DR). Methods: This cross-sectional study included patients with and without diabetes. Patients underwent comprehensive ocular examination. CT was obtained using spectral-domain optical coherence tomography (SD-OCT) with enhanced depth imaging (EDI) mode. Clinical parameters were body mass index, mean arterial pressure, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The 43 prevalence studies included 47 585 participants and their characteristics are shown in Table 1 . With respect to scientific production by country, eighteen studies were conducted in Brazil [ 30 , 32 , 33 , 35 37 , 39 42 , 44 , 50 , 54 , 58 , 59 , 65 67 ], twelve in Mexico [ 27 – 29 , 38 , 45 , 47 , 49 , 51 , 55 , 57 , 60 , 64 ], four in Cuba [ 31 , 34 , 43 , 48 ], two in Peru [ 46 , 61 ] two in Chile [ 63 , 69 ], and one in Argentina [ 68 ], Costa Rica [ 62 ], Ecuador [ 56 ], Puerto Rico [ 52 ], and Suriname [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 43 prevalence studies included 47 585 participants and their characteristics are shown in Table 1 . With respect to scientific production by country, eighteen studies were conducted in Brazil [ 30 , 32 , 33 , 35 37 , 39 42 , 44 , 50 , 54 , 58 , 59 , 65 67 ], twelve in Mexico [ 27 – 29 , 38 , 45 , 47 , 49 , 51 , 55 , 57 , 60 , 64 ], four in Cuba [ 31 , 34 , 43 , 48 ], two in Peru [ 46 , 61 ] two in Chile [ 63 , 69 ], and one in Argentina [ 68 ], Costa Rica [ 62 ], Ecuador [ 56 ], Puerto Rico [ 52 ], and Suriname [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the populations assessed, in twenty-four studies the participants were assessed in the hospital [ 29 , 32 35 , 37 41 , 44 – 46 , 49 – 52 , 56 – 58 , 62 , 65 , 67 , 68 ], ten in the community [ 18 , 19 , 21 , 33 , 34 , 38 , 44 , 46 , 50 , 51 ], and nine in primary care [ 31 , 36 , 48 , 54 , 61 , 63 , 64 , 66 , 69 ]. For the type of DM, eight studies assessed T1DM [ 32 , 34 , 35 , 39 , 40 , 44 , 50 , 58 ], eighteen T2DM [ 27 , 33 , 37 , 41 , 42 , 45 , 46 , 48 , 49 , 51 , 54 –…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also shown a change in choroidal thickness with fluctuation in plasma glucose levels. These findings indicate that the choroid is a more dynamic tissue than the retina [ 42 , 43 , 44 ]. However, our results show that the severity of microangiopathy is comparable in the retina and underlying choroid [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, these two factors were associated with SF-CT both in univariable and multivariable analyses in patients with DM without DR. Fasting blood sugar was associated with a thinner SF-CT, and HbA1c was associated with thicker SF-CT. In a study evaluating the influence of glycemic parameters on CT in patients with DM without DR and in patients with DM and DR, Abalem et al found a positive correlation between capillary blood glucose and CT in patients with NPDR, but not in those with PDR [ 44 ]. However, they found no correlation of fasting blood sugar and HbA1c with CT. Torabi et al investigated the correlation between CT and HbA1c in patients with type 2 diabetes in an SD-OCT study in which both eyes from patients with diabetes were divided into three groups according to HbA1c values ( ≤7% good control, 7–8% moderate control and ≥8% poor control) and concluded that there is a significant correlation of CT with HbA1c in patients with DM, and an HbA1c ≤ 7% may prevent choroidal thinning [ 45 ].…”
Section: Discussionmentioning
confidence: 99%